The Effect of Board Gender Diversity on Dividend Payments : Evidence from Indonesia - Eldinar Isty Fauziah; Agung Nur Probohudono; Doddy Setiawan (Australasian Accounting, Business and Finance Journal, 2022)
This research aims to analyze the impact of board gender diversity on dividend payments in Indonesia. Indonesia is one of the emerging economies. Some of the institutional specificities of emerging economies are the lack of protection of minority shareholders' rights, and market uncertainty may increase agency problems that raise doubts about future cash flows such as dividend payments. This research uses the data of listed firms from Indonesia Stock Exchange over the period 2013-2016. The data collection method uses purposive sampling. Indonesia implements a two-tier system that has directors and commissioners. We find evidence indicating that women directors are negatively related to the dividend payment, while women commissioners have positively related to the dividend payment. Moreover, we find that women independent directors, women executive directors, and women executive commissioners are positively associated with dividend payments, while women independent commissioners do not have an effect on dividend payments. The sample in this study is limited because the payment of dividends is not a necessity. This study provides the view that board gender diversity can create systems that make better decisions and encourage women to have a chance to participate in top management.
Keywords: Board Gender Diversity; Dividend Payments; Agency Theory